An exploration into the home field, global advantage and liability of unfamiliarness hypotheses in multinational banking - Sufian, Fadzlan (Elsevier, 2011)
This paper seeks to expand the efficiency paradigm of the eclectic theory in multinational banking within the context of a developing country banking sector. We employ the Data Envelopment Analysis (DEA) method to examine the efficiency of multinational banks operating in the Malaysian banking sector from 1995 to 2007. We then employ the panel regression analysis to examine the impact of origins on bank efficiency. We find foreign banks from North America to be the most efficient banking group, providing support to the ‘limited form’ of the global advantage hypothesis. On the other hand, we do not find evidence on both the liability of unfamiliarness and home field advantage hypotheses.